(untitled) (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2025)
This study aims to analyze the influence of religious beliefs and religiosity on the work ethic of Muslim traders in Sungai Penuh City. The method used is a quantitative approach, with data collected through questionnaires distributed to 104 Muslim traders. Data analysis was conducted using linear regression techniques to determine the extent to which religious beliefs and religiosity contribute to work ethic. The results show that religious beliefs have a significant positive effect on the work ethic of traders, where religious values motivate them to work harder and more honestly. Additionally, religiosity also significantly contributes to the enhancement of work ethic, with traders who possess high levels of religiosity tending to demonstrate better discipline and responsibility in running their businesses. These findings are expected to provide insights for traders and policymakers in developing strategies to improve work ethic within the community, as well as to strengthen the role of religious values in the business world. This study also aims to serve as a foundation for further research on the relationship between religion, religiosity, and economic behavior in a broader context.